1994
DOI: 10.1037/0096-1523.20.4.751
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric aymmetries in adults' perception of infant emotional expressions.

Abstract: Accounts of emotion lateralization propose either overall right hemisphere (RH) advantage or differential RH versus left hemisphere (LH) involvement depending on the negative-positive valence of emotions. Perceptual studies generally show RH specialization. Yet viewer emotional responses may enhance valence effects. Because infant faces elicit heightened emotion in viewers, perceptual asymmetries with chimeric infant faces were assessed. First, it was determined that chimeras must be paired with their counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Interestingly, for fearful stimuli, differences were almost absent, showing a slight deactivation increase in the right visual cortex in subjects with ASDs compared to typical controls. Some investigators (Morris et al 1998(Morris et al , 1999Nomura et al 2004;Best et al 1994;Davidson and Irwin 1999) have reported right hemispheric dominance concerning unconscious negative emotional processing, although recent studies of emotional valence have failed to detect hemispheric dominance (Viinikainen et al 2010). Sato and Aoki (2006) have speculated that right hemispheric dominance in unconscious negative emotional processing may not be specific to facial stimuli.…”
Section: Valence and Primary Visual Areasmentioning
confidence: 94%
“…Interestingly, for fearful stimuli, differences were almost absent, showing a slight deactivation increase in the right visual cortex in subjects with ASDs compared to typical controls. Some investigators (Morris et al 1998(Morris et al , 1999Nomura et al 2004;Best et al 1994;Davidson and Irwin 1999) have reported right hemispheric dominance concerning unconscious negative emotional processing, although recent studies of emotional valence have failed to detect hemispheric dominance (Viinikainen et al 2010). Sato and Aoki (2006) have speculated that right hemispheric dominance in unconscious negative emotional processing may not be specific to facial stimuli.…”
Section: Valence and Primary Visual Areasmentioning
confidence: 94%
“…Best et al, 1994;Davidson, 1992]. However, on the basis of their meta-analysis of fMRI and PET studies, Wager et al [2003] concluded that the lateralization hypothesis does not hold for the whole brain.…”
Section: Laterality Of Valence Processingmentioning
confidence: 96%
“…No medication, except birth-control pills, was allowed. Psychiatric disorders were excluded using the Mini-International Neuropsychiatric Interview (Mini [52]) and the Dutch translation of the Beck Depression inventory (BDI [7]). Female volunteers with a psychiatric disorder and/or a score higher than eight on the BDI were excluded.…”
Section: Participantsmentioning
confidence: 99%